1998
DOI: 10.1038/sj.jhh.1000581
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the acute arterial effects of converting enzyme inhibition in essential hypertension: a double-blind, comparative and crossover study

Abstract: In subjects with essential hypertension, angiotensinconverting enzyme (ACE) inhibition increases arterial diameter, compliance and distensibility of peripheral muscular arteries in association with blood pressure reduction. Whether pulse pressure amplification is modified by ACE inhibition and whether changes in compliance and distensibility are due to a drug effect on the arterial wall, to the blood pressure reduction or to a combination of both factors, is largely ignored. In a randomised, double-blind cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 20 publications
2
16
0
4
Order By: Relevance
“…15,16 Although we did not measure pulse-wave velocity in our study, we speculate that quinapril may have favourably affected the timing of wave reflection as well (due to a decrease in arterial stiffness), because (i) quinapril increased both Dt and PP amplification (though nonsignificantly, since our sample size was not powered to detect a significant change of these parameters) and (ii) quinapril improved brachial artery responses (FMD) mediated by NO, which is an important determinant of arterial stiffness. 37 This is in line with evidence showing that quinapril reduces predominantly the stiffness of musculartype arteries, 44 such as the brachial artery and abdominal aorta.…”
Section: Central Haemodynamicssupporting
confidence: 77%
“…15,16 Although we did not measure pulse-wave velocity in our study, we speculate that quinapril may have favourably affected the timing of wave reflection as well (due to a decrease in arterial stiffness), because (i) quinapril increased both Dt and PP amplification (though nonsignificantly, since our sample size was not powered to detect a significant change of these parameters) and (ii) quinapril improved brachial artery responses (FMD) mediated by NO, which is an important determinant of arterial stiffness. 37 This is in line with evidence showing that quinapril reduces predominantly the stiffness of musculartype arteries, 44 such as the brachial artery and abdominal aorta.…”
Section: Central Haemodynamicssupporting
confidence: 77%
“…There has been a recent surge in interest in drugs that not only reduce blood pressure but also modify the blood pressure curve. In this setting, nitrates, 27 calcium-channel blockers, 15 vasodilating beta-blockers 10 and ACE inhibitors [12][13][14] have all been shown to decrease AWR in the ascending aorta. This is in contrast to drugs that have no effect on AWR and arterial stiffness despite the same extent of blood pressure reduction.…”
Section: Valsartan-induced Effects On Arterial Wave Reflectionmentioning
confidence: 99%
“…27 In genetically hypertensive rats that have equal central and peripheral pressures, giving ACE inhibitors or calcium-channel blockers restores the pulse pressure gradient but hydralazine does not. 18 However, there is evidence that ACE inhibitors, by causing an equal decrease in brachial and aortic PP may not actually increase PP amplification, despite reducing wave reflection in patients with essential hypertension 14 although some studies have shown a restoration of pulse pressure gradient in patients with end-stage renal disease. 13 In the present study, we have observed that valsartan when added to an ACE inhibitor, preferentially decreased central pulse pressure, favourably modifying pulse pressure amplification, restoring it to normal values.…”
Section: Pulse Pressure Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Topouchian 44 showed that the acute administration of quinapril increased carotid artery distensibility and decreased PWV and wave reflections, an effect that was in part independent of BP reduction. A number of other studies have confirmed that other ACE-Is similarly reduce arterial stiffness (see Table 3).…”
Section: Ace Inhibitorsmentioning
confidence: 99%